CHARACTERISTICS OF COOKIES FORTIFIED WITH 2 GRAM Chlorellasp. POWDER - Aulia Faradila; Suparmi Suparmi; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT            This study aimed to determined the effect of cookies fortified with 2gram Chlorella sp. powder on cookies on consumer acceptabilityand nutritional value of cookies Chlorella sp. This research method was experimental and descriptive, consisted of the manufacture of Chlorella sp. powder and the manufacture of cookies Chlorella sp. The test parameters observed were organoleptic and proximate. The results showed that the characteristics of the cookies Chlorella sp. light green color, slightly fragrant cookies, crunchy texture, and sweet taste with nutritional value of protein equal to 9,78%, fat 25,27%, water 3,13%, ash 1,56%, and carbohydrates 60,26%.Keywords: Chlorella sp., Cookies, Nutritional value, Consumer acceptability